Lifetime Driver's License Policy - Nur Dianawati; Jayanti Armida Sari (Nakhoda: Jurnal Ilmu Pemerintahan)
The Lifetime Driver's License Policy has sparked debate in Indonesia. This research examines the challenges and opportunities of implementing a lifetime driving license policy in Indonesia. This study employs a literature review as a fundamental technique for comprehensive understanding; the research utilizes the SOAR analysis approach to formulate implementation strategies. This study concludes that the implementation of a lifetime driver's license policy have substantial potential to enhance administrative efficiency, reinforce service integrity, promote public awareness and adherence to traffic regulations, and contribute to overall road safety improvements. The recommended strategies include fostering service transparency, strengthening supervision and law enforcement, digitalizing service processes, raising public awareness through socialization and education, enhancing service quality, improving driver competence through training, streamlining bureaucratic procedures, and actively involving the community.